(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve students’ ability to listen to the elements of poetry building using the Problem Based Learning (PBL) learning model in class X SMK Negeri 1 Lolomatua in the 2024/2025 Learning Year. This classroom action research (PTK) uses a four-stage procedure: planning, action, observation, and reflection, which is carried out in two cycles. The research subjects were 24 students. Data were collected through observation techniques, tests, field notes, and documentation. The results showed a significant improvement. In cycle I, the average student score only reached 52.6%, with the lowest score of 37.5 and the highest of 75. Student activeness in this cycle was in the range of 75% to 80.8%. Meanwhile, in cycle II, the average student score increased sharply to 80%, with the lowest score of 62.7 and the highest of 100. Student activeness also increased to 92.5% at the first meeting and 95.4% at the second meeting. This increase was supported by the performance of researchers who successfully carried out all stages of learning with a percentage of 100% at the end of cycle II. Based on these findings, it can be concluded that the application of the Problem Based Learning learning model is effective in improving the ability to listen to the elements of poetry building in students.